Electronic government : 15th IFIP WG 8.5 International Conference, EGOV 2015, Guimarães, Portugal, September 5-8, 2016, Proceedings /: 15th IFIP WG 8.5 International Conference, EGOV 2015, Guimarães, Portugal, September 5-8, 2016, Proceedings. (2016) - Unknown
No abstract available